2019
DOI: 10.1103/physreva.99.052702
|View full text |Cite
|
Sign up to set email alerts
|

Radiative electron capture as a tunable source of highly linearly polarized x rays

Abstract: The radiative electron capture (REC) into the K shell of bare Xe ions colliding with a hydrogen gas target has been investigated. In this study, the degree of linear polarization of the K-REC radiation was measured and compared with rigorous relativistic calculations as well as with the previous results recorded for U 92+ . Owing to the improved detector technology, a significant gain in precision of the present polarization measurement is achieved compared to the previously published results. The obtained dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As widely used experimental facilities at present, both electron beam ion traps and ion storage rings can provide nearly unidirectional and monoenergetic electron or ion beams [6,7]. When combined with modern high-resolution x-ray spectrometers or polarimeters, they were often employed to study angular distribution and linear polarization of characteristic x-ray lines emitted following various relativistic electron-ion collision processes, such as, electron-impact excitation (EIE) [8][9][10][11][12][13][14][15][16][17], dielectronic recombination [18][19][20][21][22][23][24][25][26], radiative electron capture (REC) [27][28][29][30][31], and nonradiative electron capture [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…As widely used experimental facilities at present, both electron beam ion traps and ion storage rings can provide nearly unidirectional and monoenergetic electron or ion beams [6,7]. When combined with modern high-resolution x-ray spectrometers or polarimeters, they were often employed to study angular distribution and linear polarization of characteristic x-ray lines emitted following various relativistic electron-ion collision processes, such as, electron-impact excitation (EIE) [8][9][10][11][12][13][14][15][16][17], dielectronic recombination [18][19][20][21][22][23][24][25][26], radiative electron capture (REC) [27][28][29][30][31], and nonradiative electron capture [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was reported that the detector technology for the measurement of the linear photon polarization (appearing in the Kshell radiative electron capture by heavy ions) was significantly improved [39].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] But also in the laboratory it is desirable and often necessary to take into account the polarization characteristics of incoming and outgoing particles to provide the most rigorous tests of our theoretical understanding of the underlying processes. A lot of radiative processes, such as X‐ray scattering, [ 3,4 ] ion–atom collisions [ 5 ] and radiative electron capture, [ 6 ] exhibit distinct polarization features, thus a complete measurement must also include the polarization analysis of the process. Moreover, it was recently shown that X‐ray polarimetry can also be used as a tool for monitoring the polarization of particle beams, such as electrons [ 7 ] or ions.…”
Section: Introductionmentioning
confidence: 99%
“…Within the Stored Particles Atomic Physics Research Collaboration (SPARC), [ 10,11 ] covering atomic physics at GSI and FAIR, several X‐ray detectors were developed on the basis of large double‐sided segmented semiconductor crystals that are well suited for the application as Compton polarimeters. In the recent years, these detectors enabled measurements of the polarization transfer in Rayleigh scattering [ 12 ] as well as in the Bremsstrahlung process [ 7 ] as well as the polarization characteristics of photons emitted by radiative electron capture [ 6 ] , and of characteristic transitions within highly charged, heavy ions. [ 13 ] Recently, a dedicated Si(Li) Compton polarimeter was commissioned that features a significantly improved energy resolution of about 1 keV at a photon energy of 60 keV.…”
Section: Introductionmentioning
confidence: 99%